The Correlation Between Chronic Energy Deficiency And Anaemia In Pregnant Women With Low Birth Weight - Laura, Disna; Reza, Hanif; Dewi, Arini (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Low birth weight (LBW) has been identified as a significant factor that can compromise intrauterine growth. In Indonesia, LBW cases are still quite high, with influential maternal factors, including chronic energy deficiency (CED) and anaemia. It is well-established that the food intake consumed during pregnancy affects the incidence of CED and anaemia. Aim: To determine the correlation of chronic energy deficiency and anaemia with LBW in East Semarang. Methods: This study used an analytical observational study with case control. There were 100 samples divided into 50 LBW (case) and 50 non-LBW (control) in the East Semarang Health Center working area. Samples were obtained from Karangdoro Health Center Medical Records from January 2021 to December 2022. The sampling technique employed consecutive sampling. The research data was tested using Chi-square test.. Results: The results of the analysis test indicated a correlation between chronic energy deficiency and LBW with a p-value of 0,000 and anaemia with LBW with a p-value of 0,001. The odd ratio result on CED is 12,966, while the odd ratio on anaemia is 4,030.. Conclusion: This study can be concluded that CED and anaemia have an influence on LBW.